The effect of journal metrics on academic resume assessment. Issue 11 (2nd November 2022) - Anderson, Craig G.; McQuaid, Ronald W.; Wood, Alex M.
ABSTRACT: It has been widely argued that journal metrics are used in assessing publication records on resumes for academic jobs and assessments. Within that debate, two important considerations emerge. Firstly, academics belonging to different career cohorts may have different experiences which are reflected in their recommendations related to targeting and assessing publication records. Secondly, recruitment or assessment expectations that include publishing in highly rated journals may lead to the targeting of a smaller number of high rated publications, with perceived lower rated journal outlets being discouraged. Using an experimental design, an online survey collected data from 1011 academics across management and psychology disciplines in the UK and USA, exploring the association between journal ratings, the number of publications on a resume, and the length of time spent in academia. Analysis indicated that when assessing an academic resume, the discouraging of lower rated journal publications may be dependent on the length of time spent in academia. Specifically, in the context of exactly the same high rated journal publications on a resume, those who had been in academia for 10–20 years were less favorable towards the inclusion of additional low rated journals. The findings contribute to how we view the socialization of institutional influences on career decision making in higher education. The results add to emergent evidence of behavioral responses to the institutional pressures on academic careers, and how individuals at different career stages may be impacted differently. This has implications for the management of academic career progression and academic recruitment processes.